MicroRNA172b-5p/trehalose-6-phosphate synthase module stimulates trehalose synthesis and microRNA172b-3p/AP2-like module accelerates flowering in barley upon drought stress - Swida-Barteczka, Aleksandra; Pacak, Andrzej; Kruszka, Katarzyna; Nuc, Przemyslaw; Karlowski, Wojciech M.; Jarmolowski, Artur; Szweykowska-Kulinska, Zofia (Frontiers in Plant Science, 2023)
MicroRNAs (miRNAs) are major regulators of gene expression during plant development under normal and stress conditions. In this study, we analyzed the expression of 150 conserved miRNAs during drought stress applied to barley ready to flower. The dynamics of miRNAs expression was also observed after rewatering. Target messenger RNA (mRNAs) were experimentally identified for all but two analyzed miRNAs, and 41 of the targets were not reported before. Drought stress applied to barley induced accelerated flowering coordinated by a pair of two differently expressed miRNAs originating from a single precursor: hvu-miR172b-3p and hvu-miR172b-5p. Increased expression of miRNA172b-3p during drought leads to the downregulation of four APETALA2(AP2)-like genes by their mRNA cleavage. In parallel, the downregulation of the miRNA172b-5p level results in an increased level of a newly identified target, trehalose-6-phosphate synthase, a key enzyme in the trehalose biosynthesis pathway. Therefore, drought-treated plants have higher trehalose content, a known osmoprotectant, whose level is rapidly dropping after watering. In addition, trehalose-6-phosphate, an intermediate of the trehalose synthesis pathway, is known to induce flowering. The hvu-miRNA172b-5p/trehalose-6-phosphate synthase and hvu-miRNA172b-3p/AP2-like create a module leading to osmoprotection and accelerated flowering induction during drought.